(untitled) (Research, Society and Development, 2025)
Objective: Analyze and report the incidence of accidents and complications related to the extraction of permanent teeth in the undergraduate dentistry course at a School clinic in Teresina-Piauí. Methodology: The research is a cross-sectional study of a quantitative nature, where the incidence of accidents and complications in dental extractions occurring in a teaching clinic of a Faculty of Dentistry was evaluated, by applying a questionnaire in the immediate and 1-week post-operative periods, checking the occurrence of any accident and/or complication associated with the surgical procedure. All participants were informed about the research and agreed to participate by signing the Free and Informed Consent Form. Result: The most prevalent accident was root fracture (6.45%), followed by soft tissue injuries (3.23%) and the simultaneous occurrence of root fracture and soft tissue injury (1.61%). Regarding complications, the most common was trismus (4.84%), followed by edema (3.23%) and a simultaneous case of trismus and edema (1.61%). Conclusion: Accidents and complications can occur in any tooth extraction surgery. In this way, a correct anamnesis, an adequate treatment plan, and the execution of a precise technique can reduce both the trauma of the procedure and the surgical time itself, which are fundamental factors in the incidence of accidents and complications.